Hermeneutika Sebagai Metoda Interpretasi Teks al-Qur’an - Khoiroh, Muflikhatul (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2012)
Hermeneutics is part of the study of philosophy that aims to understand and interpret texts (including religious texts) elusive becomes easy, and explain the meaning of the text as objectively as possible. In the process of understanding and interpretation of the text, will always appear the assumption that there are three entities involved, namely the world author, the world of the text, and world readers. If any of the three subjects that far from each other, either because of time, place and culture, the text becomes a thing alien to readers. In such circumstances, the text easily misunderstood. For this reason, the theory of text interpretation, which is commonly known as hermeneutics, is indispensable. Areas of arable hermeneutics is covering text, context and contextual